Peran Moderasi Altruisme: Literasi Zakat, Pendapatan dan Minat Muzakki - Ahmad Wira; Hulwati; Roihan Habibi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to look at the moderating role of altruism in influencing zakat literacy and income on muzakki intention whether the role of altruism is able to strengthen or otherwise weaken the interest of muzakki at the Dompet Dhuafa Singgalang institution. The methodology in this research is a quantitative approach by applying SmartPLS 3.0 software. Primary data was obtained through distributing questionnaires to Dompet Dhuafa Singgalang donors. The sample was taken through the purposive sampling technique method and the calculation of the sample size using the Isaac and Michael formula resulted in 360 respondents. the results of these findings provide the fact that the direct effect of altruism and muzakki intention has a positive but insignificant effect. While the direct effect of zakat literacy and income variables on muzakki intention has a positive and significant effect. Furthermore, the moderating role of altruistic is not able to provide a moderating effect on the effect of zakat literacy and muzakki intention, so it can be said that the moderating role of altruistic weakens the moderating effect. The role of altruistic is also unable to provide a moderating effect on income and muzakki intention, so it can be categorized that the moderating role of altruistic weakens the moderating effect.